Small-molecule drugs development for Alzheimer's disease - Yao, Weiwei; Yang, Huihui; Yang, Jinfei (Frontiers in Aging Neuroscience, 2022)
Alzheimer's disease (AD) is an irreversible, progressive neurodegenerative brain disorder with no effective therapeutic drugs currently. The complicated pathophysiology of AD is not well understood, although beta-amyloid (Aβ) cascade and hyperphosphorylated tau protein were regarded as the two main causes of AD. Other mechanisms, such as oxidative stress, deficiency of central cholinergic neurotransmitters, mitochondrial dysfunction, and inflammation, were also proposed and studied as targets in AD. This review aims to summarize the small-molecule drugs that were developed based on the pathogenesis and gives a deeper understanding of the AD. We hope that it could help scientists find new and better treatments to gradually conquer the problems related to AD in future.